Degradation of ciprofloxacin in aqueous solution using ozone microbubbles: spectroscopic, kinetics, and antibacterial analysis. Issue 8 (August 2022) - Verinda, Sera Budi; Muniroh, Muflihatul; Yulianto, Eko; Maharani, Nani; Gunawan, Gunawan; Amalia, Nur Farida; Hobley, Jonathan; Usman, Anwar; Nur, Muhammad
Abstract: Ciprofloxacin (CIP) has been listed in the last version of the surface water due to its ability to kill human cells by inhibiting the activity of DNA topoisomerase IV. Thus, CIP, along with other antibiotic pollution has become a serious threat to the environment and public health. Ozonation has been used as an advanced technique that is applied in wastewater treatment to remove CIP, but the primary limitation of this method is the low solubility of ozone in water. This study is the first report of CIP removal in a scale-up of its aqueous solution using a self-developed aerator pump-enhanced ozonation (APO) system, which only employs a propeller and a zigzag arrangement of meshes. This aerator pump decreased the size of ozone bubbles by 90% and increased the effective ozone solubility to 0.47 ppm. The mechanism of degradation of CIP is attributed to an oxidation reaction of the antibiotic with reactive oxygen species, such as hydroxyl, oxygen, and hydroperoxyl radicals, generated on the surface of the ozone microbubbles. It was found that the rate and efficiency of degradation of CIP using the APO system were 3.64 × 10 −3 /min and 83.5%, respectively, which is higher compared with those of conventional flow ozonation (FO) systems (1.47 × 10 −3 /min and 60.9%). The higher degradation efficiency of CIP by the APO system was also revealed by its higher electrical energy efficiency (0.146 g/kWh), compared to that of the FO system (0.106 g/kWh). The degradation of CIP was also monitored by the resulting antibacterial activity against Escherichia coli and Staphylococcus aureus . Graphical abstract: Image 1 Abstract : Ciprofloxacin; Antibiotic contaminants; Degradation; Ozone; Microbubbles.